2014
DOI: 10.1037/a0035780
|View full text |Cite
|
Sign up to set email alerts
|

Repetition reduction: Lexical repetition in the absence of referent repetition.

Abstract: Repeated words are produced with reduced acoustic prominence compared to words that are new to a discourse. Although these effects are often attributed to priming in the production system, the locus of the effect within the production system remains unresolved because in natural speech, repetition often involves repetition of referents and lexical items simultaneously. Therefore, repetition reduction could be due to repeated mention of a referent, or repetition of a word or referring expression. In our study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
4
46
1
Order By: Relevance
“…First of all, participants in our experiments are not actually addressing an audience in the task, and repetition reduction was still observed. Furthermore, the presence of an audience has been shown in several similar studies to not be necessary for repetition reduction (Lam & Watson, 2010; Lam & Watson, 2014; Kahn & Arnold, 2015). Of course, it is possible that speakers assume that there is a virtual listener for any speech they produce, and then adjust their linguistic choices accordingly.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…First of all, participants in our experiments are not actually addressing an audience in the task, and repetition reduction was still observed. Furthermore, the presence of an audience has been shown in several similar studies to not be necessary for repetition reduction (Lam & Watson, 2010; Lam & Watson, 2014; Kahn & Arnold, 2015). Of course, it is possible that speakers assume that there is a virtual listener for any speech they produce, and then adjust their linguistic choices accordingly.…”
Section: Methodsmentioning
confidence: 91%
“…We, however, were interested in the factors that lead to repetition reduction on a target noun that was repeated or not (e.g. Kahn & Arnold, 2015; Lam & Watson, 2010; Lam & Watson, 2014). Experiments 1 and 2 found that the repetition of a word that was previously produced as mouthed or unmouthed inner speech resulted in a reduction in target word onset time, but not target word duration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For English, Lam and Watson (2010) found intensity increases as markers of discourse relations (i.e., unexpected mentions of referents had higher intensity), while word duration was more dependent on production constraints (i.e., repeated occurrences of referring expressions were shorter, see also, Bard et al, 2000;Lam & Watson, 2014). Durations of verbally repeated occurrences of given referents were shorter in contrast to productions repeating a referent that was displayed visually previously (Kahn & Arnold, 2012).…”
Section: Multiple Cues To Saliencementioning
confidence: 91%